Parties and party politics in India - Hasan, Zoya (ed.); Hasan, Zoya (ed.) (New Delhi Oxford University Press, 2004)
Presenting a collection of articles on the politics and party system in India, this book examines the Congress system, the national parties, as well as the regional parties. Discussed in terms of their connection with caste, class, and communal and regional politics, these parties are also analyzed by their impact on the changing nature of Indian politics.
Keywords: Political Parties-India; Party politics-India; Politics and governance-India